2001
DOI: 10.1111/0033-3352.00137
|View full text |Cite
|
Sign up to set email alerts
|

The Varieties of Faith‐Related Agencies

Abstract: Smith is an associate professor of public affairs at the Daniel J. Evans School of Public Affairs at the University of Washington. He is also editor of Nonprofit and Voluntary Sector Quarterly. His recent publications examine the transformation of social services, new approaches to policy analysis, systems change in workforce-development programs, and the government-nonprofit relationship. His ongoing research focuses on the role of religion in nonprofit service agencies and the restructuring of social service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
143
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 49 publications
0
143
1
Order By: Relevance
“…Many scholars and policymakers alike presumed that organizations offering secularized services would become more secular over time [45]. Starting with a Reagan-era speech, these large, multi-service non-profits were equated with the uncaring, bureaucratic services of government ( [3], p. 23).…”
Section: Charitable Choice Fbni and The Role Of Faith-based Organizamentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars and policymakers alike presumed that organizations offering secularized services would become more secular over time [45]. Starting with a Reagan-era speech, these large, multi-service non-profits were equated with the uncaring, bureaucratic services of government ( [3], p. 23).…”
Section: Charitable Choice Fbni and The Role Of Faith-based Organizamentioning
confidence: 99%
“…While critics argued for separation of church and state through a variety of mechanisms, both scholars and policymakers attempted to identify the faith base in organizations, so that they could determine if openly religious providers were "better" than secular nonprofits or those that did not use religious elements in their programming. Numerous scholars and a policy committee created a series of scales, most relying on outward signs of religiosity, to identify the level of faith in an organization [15,45,[47][48][49]. Generally, the scales included a number of gradations varying from secular to faith integrated, with the faith-integrated programs using prayer and other religious elements in their programming and generally suffusing religion throughout their programs.…”
Section: Charitable Choice Fbni and The Role Of Faith-based Organizamentioning
confidence: 99%
“…Jeavons (1997) proposed seven dimensions and these were also enumerated by Sider and Unruh (2004) as, "organizational self-identity, selection of organizational participants (staff, volunteers, funders, and clients), sources of resources, goals, products, and services (including "spiritual technologies"), information processing and decision making (e.g., reliance on prayer and religious precepts for guidance), the development and distribution of organizational power, and organizational fields (including program partners)" (p. 111). Smith and Sosin (2001) also analyzed several institutions to study how faith is present in an organization and suggested that the presence of faith can be found in the form of "resource dependency, authority and organizational culture". The availability of funds, control of religious institutions or personalities, the influence of faith in the organizational design are some of the important factors that they found to be shaping the uniqueness of faith-based organizations.…”
Section: Identification Of Faith-based Organizationsmentioning
confidence: 99%
“…So, in a highly involved organization, it may be mandatory for the staff to attend the prayers or rituals whereas it may be voluntary in other cases. Jeavons (1997Jeavons ( , 2004 organizational self-identity, selection of organizational participants (staff, volunteers, funders, and clients), sources of resources, goals, products, and services (including "spiritual technologies"), information processing and decision making (e.g., reliance on prayer and religious precepts for guidance), the development and distribution of organizational power, and organizational fields (including program partners) Smith and Sosin (2001) resource dependency, authority and organizational culture Berger (2003) Not only in programmes but pervasiveness of faith Unruh (2004) Self-descriptions, sacred objects, invitations to religious activities, prayer, use of sacred texts, worship, sharing of personal testimonies, religious teachings, and invitations to a personal faith commitment Ebaugh et al (2006) Service, Staff, and Organizational dimensions Goggin and Orth (2002) Faith Integration Scale (organization, administration, environment, funding, and programme) Aiken (2010) change in the community; theology and development goals; selection of beneficiaries; programme design and implementation; staff motivation and faith in internal practice James (2004) structural affiliation and governance; values and staff motivation; mission; strategy and theory of development; selection of partners and choice of beneficiaries; faith practices and teaching in programming; staffing and leadership; organisational culture and decision-making; constituency and sources of funding; and external relationships Source: Literature Survey…”
Section: Influence Of Faith In Fbosmentioning
confidence: 99%
“…The new actors are congregations that are not required to incorporate and fundamental religious groups (formerly described by the U.S. Supreme Court as "persuasively sectarian") that are incorporated but refused public funds because they perceived it as "going secular." In fact, three recent studies showed that some faith-based providers lost their religious edge and became more secular after receiving public funds (Campbell, 2002;Chambre, 2001;Smith & Sosin, 2001). …”
Section: Charitable Choicementioning
confidence: 99%